Iridium unit point modified cobalt spinel electrocatalytic material and electrocatalyst
Patent Information
- Application Number
- CN202210233074.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-03-09
AI Technical Summary
In existing electrochemical water splitting devices, the high overpotential and slow reaction kinetics of the oxygen evolution reaction limit the overall reaction efficiency, and existing catalysts are either costly or have poor stability.
Ir-Co3O4, a cobalt spinel electrocatalytic material modified with iridium unit sites, enhances the catalytic performance of the oxygen evolution reaction through the synergistic effect of the nanosheet structure and iridium unit sites. It can also be prepared using a simple grinding and calcination process, thus reducing costs.
Exhibiting high catalytic activity and stability under acidic conditions, the iridium-modified cobalt spinel electrocatalyst demonstrates excellent catalytic performance and low cost in the oxygen evolution reaction, making it suitable for electrochemical water splitting devices.
Smart Images

Figure CN116770323B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic materials, specifically to a cobalt spinel electrocatalytic material and electrocatalyst modified with iridium unit sites. Background Technology
[0002] Hydrogen, with its high energy density and zero carbon emissions, is a clean and sustainable energy source that can effectively address the fossil fuel crisis. Electrochemical water splitting is considered one of the most promising pathways for hydrogen production. The water electrolysis reactor contains two half-reactions: hydrogen evolution at the cathode and oxygen evolution at the anode. The oxygen evolution reaction, due to its large overpotential and slow reaction kinetics, is considered the main bottleneck limiting the overall reaction efficiency. Therefore, developing a highly efficient electrocatalyst to accelerate the oxygen evolution reaction at the anode is of great significance for improving the efficiency and widespread application of electrochemical water splitting devices.
[0003] Currently, there are two main types of electrochemical oxygen evolution reaction (OER) catalysts of interest. One type consists of non-noble metal oxide materials based on iron, cobalt, and nickel. These are abundant, inexpensive, and possess certain catalytic activity. However, these oxide materials are highly susceptible to dissolution under acidic conditions, resulting in poor catalytic stability. The other type comprises noble metal catalysts such as ruthenium and iridium. These catalysts can effectively enhance the catalytic performance of the OER as electrocatalysts, but their high price and scarcity severely hinder their large-scale application. Therefore, combining high catalytic performance with low cost is the primary requirement for the development of OER electrocatalysts.
[0004] Single-atom / unit-site catalysts have attracted widespread attention from researchers in recent years due to their advantages such as uniform distribution of active sites, wide range of supports, high atom utilization efficiency, and low amount of precious metals required in electrochemical reactions. Summary of the Invention
[0005] This invention is made to solve the above-mentioned problems, and its purpose is to provide a cobalt spinel electrocatalytic material and electrocatalyst modified with iridium unit sites.
[0006] This invention provides an iridium-modified cobalt spinel electrocatalytic material, characterized in that the chemical formula of the iridium-modified cobalt spinel electrocatalytic material is abbreviated as Ir-Co3O4, and the iridium in the iridium-modified cobalt spinel electrocatalytic material exists in the cobalt spinel in the form of single dots.
[0007] The iridium-modified cobalt spinel electrocatalytic material provided by this invention may also have the following characteristics: the iridium-modified cobalt spinel electrocatalytic material has a nanosheet structure with a thickness of 2 nm to 4 nm, and the atomic ratio of Ir, Co, and O in the iridium-modified cobalt spinel electrocatalytic material is 1.05:27.43:71.52.
[0008] The iridium-modified cobalt spinel electrocatalytic material provided by this invention may also have the following characteristics, and its preparation method includes the following steps: Step 1, cobalt chloride hexahydrate, anhydrous iridium chloride and sodium chloride are initially mixed evenly in an agate mortar to obtain a mixed powder; Step 2, the mixed powder is ground and sodium hydroxide solution is added to obtain a mixture; Step 3, the mixture is placed in an oven to dry, the dried mixture is ground in an agate mortar, and then placed in a muffle furnace to react at a predetermined temperature for a predetermined time, washed, and dried to obtain the iridium-modified cobalt spinel electrocatalytic material.
[0009] The cobalt spinel electrocatalytic material modified with iridium unit sites provided by the present invention may also have the following characteristics: wherein, in step 1, the molar ratio of cobalt chloride hexahydrate and anhydrous iridium chloride as precursors is 20:1.
[0010] The cobalt spinel electrocatalytic material modified with iridium unit sites provided by the present invention may also have the following characteristics: wherein, in step 1, the mass ratio of cobalt chloride hexahydrate to sodium chloride is 476 mg: 500 mg.
[0011] The cobalt spinel electrocatalytic material modified with iridium unit sites provided by this invention may also have the following characteristics: wherein the specific process of step 2 is as follows:
[0012] The mixed powder was placed in a high-energy ball mill jar and milled at 500 rpm for 1 hour. Then, sodium hydroxide solution was added, and the mixture was milled again at 500 rpm for 1 hour. The concentration of the sodium hydroxide solution was 4M, and the mass-volume ratio of the mixed powder to the sodium hydroxide solution was (0.9g~1.1g):1mL.
[0013] The cobalt spinel electrocatalytic material modified with iridium unit points provided by the present invention may also have the following characteristics: wherein, in step 3, the mixture is placed in an oven and dried at a temperature of 60°C for 12 hours.
[0014] The cobalt spinel electrocatalytic material modified with iridium unit points provided by the present invention may also have the following characteristics: in step 3, the predetermined temperature is 350°C, the predetermined time is 6 hours, and the sintering gas in the muffle furnace is air.
[0015] The present invention provides an electrocatalyst, characterized in that it comprises: the above-mentioned cobalt spinel electrocatalytic material modified with iridium unit sites and carbon powder.
[0016] The electrocatalyst provided by the present invention may also have the following feature: wherein the electrocatalyst is formed by grinding and mixing cobalt spinel electrocatalytic material modified with iridium unit sites and carbon powder in a mass ratio of 1:1.
[0017] The role and effect of invention
[0018] The iridium-modified cobalt spinel electrocatalytic material (chemical formula Ir-Co3O4) according to the present invention maximizes the atomic utilization of the noble metal iridium because the iridium exists in the form of a single point in the cobalt oxide spinel structure. At the same time, the single point iridium, as the main active site, has a synergistic effect with the surrounding cobalt atoms, which can effectively regulate the electronic structure and improve the oxygen evolution performance of the material. This structural design enables cobalt spinel to have high oxygen evolution catalytic activity under acidic conditions and has broad application prospects.
[0019] Furthermore, because Ir-Co3O4 has an ultrathin sheet-like structure, more iridium unit sites can be exposed on the surface, providing a larger active surface area for the contact between the electrolyte and the catalyst, which can effectively improve the oxygen evolution catalytic performance of the catalyst.
[0020] In addition, the electrocatalyst made from the above-mentioned Ir-Co3O4 and carbon powder mixture exhibits high catalytic activity in the oxygen evolution reaction.
[0021] Furthermore, since the above-mentioned method for preparing Ir-Co3O4 employs a simple grinding and calcination process, and the precursors cobalt chloride hexahydrate and anhydrous iridium chloride are non-toxic and readily available, the method for preparing Ir-Co3O4 has the advantages of being safe, reliable, simple, efficient, and easy to scale up, and can synthesize gram-scale catalysts in a single step.
[0022] Furthermore, because this preparation method only requires the addition of a small amount of the noble metal precursor iridium chloride to prepare a highly active cobalt spinel electrocatalyst material with iridium unit site modification (chemical formula abbreviation Ir-Co3O4), this invention has the advantages of low cost. Attached Figure Description
[0023] Figure 1 These are the X-ray diffraction (XRD) pattern and simulated spectrum of Example 1 (Ir-Co3O4);
[0024] Figure 2 This is an atomic force microscopy (AFM) pattern of Example 1 (Ir-Co3O4);
[0025] Figure 3 This is a scanning electron microscope energy dispersive spectroscopy (SEM-EDX) image of Example 1 (Ir-Co3O4);
[0026] Figure 4 This is an aberration-corrected transmission electron microscope (AC-HRTEM) image of Example 1 (Ir-Co3O4);
[0027] Figure 5 This is the extended X-ray absorption fine structure spectrum (EXAFS) of Example 1 (Ir-Co3O4);
[0028] Figure 6 The X-ray diffraction (XRD) pattern and simulated spectrum of Comparative Example 1 (Co3O4) are shown. Figure 7 The oxygen evolution performance of the samples corresponding to Example 1 (Ir-Co3O4) and Comparative Example 1 (Co3O4), Comparative Example 2 (IrO2), and Comparative Example 3 (C-Co3O4) in 0.5M sulfuric acid electrolyte is shown in the graph.
[0029] Figure 8 The electrochemical impedance spectroscopy and fitting curves of the samples corresponding to Example 1 (Ir-Co3O4) and Comparative Example 1 (Co3O4), Comparative Example 2 (IrO2), and Comparative Example 3 (C-Co3O4) are shown.
[0030] Figure 9 The samples corresponding to Example 1 (Ir-Co3O4), Comparative Example 1 (Co3O4), Comparative Example 2 (IrO2), and Comparative Example 3 (C-Co3O4) are at 10 mA / cm 2 A chronoelectric potentiometer diagram under current density;
[0031] Figure 10 These are photographs of Example 1 (Ir-Co3O4) after being enlarged during the experiment;
[0032] Figure 11 This is an X-ray diffraction (XRD) pattern of Example 1 (Ir-Co3O4) after a scaled-up experiment. Detailed Implementation
[0033] To make the technical means, creative features, objectives and effects of the present invention easy to understand, the following embodiments, in conjunction with the accompanying drawings, specifically illustrate the iridium-modified cobalt spinel electrocatalytic material, its preparation method and electrocatalyst of the present invention.
[0034] <Example 1>
[0035] Example 1 provides an iridium-modified cobalt spinel electrocatalytic material (Ir-Co3O4), the preparation method of which includes the following steps:
[0036] Step 1: Place 0.476g of cobalt chloride hexahydrate, 0.029g of anhydrous iridium chloride and 0.5g of sodium chloride in an agate mortar and grind and mix them evenly to obtain a mixed powder.
[0037] Step 2: Place the mixed powder obtained in Step 1 into a high-energy ball mill jar and ball mill at 500 rpm for 1 hour. Then add 1 mL of 4M sodium hydroxide solution and continue to ball mill in the high-energy ball mill jar at 500 rpm for 1 hour to obtain the mixture.
[0038] Step 3: The mixture obtained in Step 2 was placed in an oven and dried at 60°C for 12 hours to obtain a dark brown powder. This powder was then placed in a muffle furnace and reacted at 350°C for 6 hours to obtain a black powder. The black powder was washed four times with ultrapure water at room temperature and dried in a vacuum drying oven to obtain an iridium-modified cobalt spinel electrocatalyst (Ir-Co3O4), the structural formula of which is shown below. Figure 1 As shown.
[0039] <Comparative Example 1>
[0040] Comparative Example 1 provides a pure cobalt spinel material (Co3O4), which is prepared by the following method:
[0041] 0.476 g of cobalt chloride hexahydrate and 0.5 g of sodium chloride were ground in an agate mortar to obtain a uniformly mixed powder. The uniformly mixed powder was then placed in a high-energy ball mill and milled at 500 rpm for 1 hour. After milling, 1 mL of 1M sodium hydroxide solution was added to the obtained uniform powder, and the mixture was then milled again at 500 rpm for 1 hour. The mixture obtained after milling was placed in an oven and dried at 60°C for 12 hours to obtain a dark brown powder. Subsequently, the powder was placed in a muffle furnace and reacted at 350°C for 6 hours to obtain a black powder. The black powder was washed four times with ultrapure water at room temperature and dried in a vacuum drying oven to obtain pure cobalt spinel (Co3O4).
[0042] <Comparative Example 2>
[0043] Comparative Example 2 used a commercial iridium oxide catalyst (IrO2), purchased from Beijing Innochem Technology Co., Ltd., with a purity of 99.9%.
[0044] <Comparative Example 3>
[0045] Comparative Example 3 used a commercial cobalt tetroxide catalyst (C-Co3O4), purchased from Beijing Innochem Technology Co., Ltd., with a purity of 99.5%.
[0046] <Test Example 1>
[0047] X-ray diffraction characterization
[0048] X-ray diffraction was performed on the compounds obtained in Example 1 and Comparative Example 1. The characterization results are as follows: Figure 1 , Figure 6 , Figure 11 As shown.
[0049] Figure 1 These are the X-ray diffraction (XRD) pattern and simulated spectrum of Example 1 (Ir-Co3O4) of the present invention.
[0050] like Figure 1 As shown, the structure refinement of Ir-Co3O4 was performed using the Rietveld method (Rietveld, 1969), resulting in the space group Fd-3m for Ir-Co3O4. The refinement results show that the edge lengths (a, b, c) of the unit cell after iridium doping at a single point are 8.097, and the cell volume is 530.89. The experimental and calculated spectra after structural refinement show good agreement.
[0051] Figure 6 The images show the X-ray diffraction (XRD) pattern and simulated spectrum of Comparative Example 1 (Co3O4).
[0052] like Figure 6 As shown, the structure refinement of Co3O4 was performed using the Rietveld method (Rietveld, 1969), resulting in a space group of Fd-3m for Co3O4. The refinement results show that the edge lengths (a, b, c) of the unit cell after unit-point iridium doping are 8.075, and the cell volume is 526.61, both smaller than that of Ir-Co3O4. This indicates that unit-point iridium was successfully incorporated into cobalt spinel in Ir-Co3O4. The experimental and calculated spectra after structural refinement show good agreement.
[0053] Figure 11 This is an X-ray diffraction (XRD) pattern of Example 1 (Ir-Co3O4) after a scaled-up experiment.
[0054] like Figure 11 As shown, after the scale-up experiment of Example 1 (Ir-Co3O4), it matched well with the PDF standard card PDF#74-1656, indicating that Ir-Co3O4 still has good crystallinity after scale-up and the structure has not changed.
[0055] <Test Example 2>
[0056] Atomic force microscopy characterization
[0057] Figure 2 This is an atomic force microscopy (AFM) pattern of Example 1 (Ir-Co3O4).
[0058] like Figure 2As shown, the Ir-Co3O4 in Example 1 has a nanosheet structure with a thickness of about 3 nm. This indicates that Ir-Co3O4 has an ultrathin sheet structure, which is beneficial for exposing active sites and increasing the contact area between the catalyst and the electrolyte.
[0059] <Test Example 3>
[0060] Scanning electron microscopy energy dispersive spectroscopy elemental analysis
[0061] Figure 3 This is a scanning electron microscope energy dispersive X-ray spectroscopy (SEM-EDX) image of Example 1 (Ir-Co3O4).
[0062] like Figure 3 As shown, the atomic ratio of Ir / Co / O in Ir-Co3O4 in Example 1 is 1.05 / 27.43 / 71.52, indicating that the content of the precious metal iridium is extremely low.
[0063] <Test Example 4>
[0064] Aberration-corrected transmission electron microscopy characterization
[0065] Figure 4 This is an aberration-corrected transmission electron microscope (AC-HRTEM) image of Example 1 (Ir-Co3O4).
[0066] like Figure 3 As shown, the white circles highlight the iridium atoms in Example 1 (Ir-Co3O4). It can be seen that the iridium atoms exist individually and are uniformly dispersed in the cobalt spinel, indicating that iridium exists in the cobalt spinel as individual points.
[0067] <Test Example 5>
[0068] Extended X-ray absorption fine structure spectroscopy characterization
[0069] Figure 5 This is the extended X-ray absorption fine structure spectrum (EXAFS) of Example 1 (Ir-Co3O4).
[0070] like Figure 5 As shown, the iridium species in Example 1 (Ir-Co3O4) contains only iridium-oxygen bonds and iridium-cobalt bonds, indicating that iridium exists in cobalt spinel in the form of single points.
[0071] <Test Example 6>
[0072] Catalytic performance testing of materials
[0073] The Ir-Co3O4 prepared in Example 1 and carbon powder (mass ratio 50%:50%) were placed in a glass bottle, and 1900 μL of isopropanol were added. The mixture was then ultrasonically mixed for 2 hours. 100 μL of Nafion (5 wt.%) was added to the resulting solution, and ultrasonication continued for 30 minutes. After homogenization, an appropriate amount of the mixture was coated onto the surface of a glassy carbon electrode and dried at room temperature, controlling the Ir-Co3O4 loading to be 0.255 mg / cm³. 2 The catalytic performance of the material was characterized using an electrochemical workstation.
[0074] Pure cobalt spinel (Co3O4) prepared in Comparative Example 1 was mixed with carbon black (mass ratio 50%:50%) in a glass bottle. 1900 μL of isopropanol was added, and the mixture was ultrasonically mixed for 2 hours. 100 μL of Nafion (5 wt.%) was added to the resulting mixture, and ultrasonication continued for 30 minutes. After homogenization, an appropriate amount of the mixture was coated onto the surface of a glassy carbon electrode and dried at room temperature, controlling the Co3O4 loading to be 0.255 mg / cm³. 2 The catalytic performance of the material was characterized using an electrochemical workstation.
[0075] Commercially available iridium oxide (IrO2) purchased in Comparative Example 2 was mixed with carbon black (mass ratio 50%:50%) in a glass bottle. 1900 μL of isopropanol was added, and the mixture was ultrasonically mixed for 2 hours. 100 μL of Nafion (5 wt.%) was added to the resulting mixture, and ultrasonication continued for 30 minutes. After homogenization, an appropriate amount of the mixture was coated onto the surface of a glassy carbon electrode and dried at room temperature, controlling the IrO2 loading to be 0.255 mg / cm³. 2 The catalytic performance of the material was characterized using an electrochemical workstation.
[0076] Commercially available cobalt tetroxide (C-Co3O4) purchased for Comparative Example 3 was mixed with carbon black (mass ratio 50%:50%) in a glass bottle. 1900 μL of isopropanol was added, and the mixture was ultrasonically mixed for 2 hours. 100 μL of Nafion (5 wt.%) was added to the resulting mixture, and ultrasonication continued for 30 minutes. After homogenization, an appropriate amount of the mixture was coated onto the surface of a glassy carbon electrode and dried at room temperature, controlling the C-Co3O4 loading to be 0.255 mg / cm³. 2 The catalytic performance of the material was characterized using an electrochemical workstation.
[0077] The carbon powder used in this test example was Vulcan XC-72R.
[0078] Test results are as follows Figure 7-9 As shown.
[0079] Figure 7Polarization curves of the oxygen evolution reaction in 0.5 M sulfuric acid electrolyte for the catalysts prepared in Example 1 (Ir-Co3O4) and Comparative Examples 1-3.
[0080] like Figure 7 As shown, the catalyst prepared by Ir-Co3O4 has the smallest overpotential and the best performance in the oxygen evolution reaction.
[0081] Figure 8 Electrochemical impedance spectroscopy (EIS) tests and fitting curves of the catalysts prepared in Example 1 (Ir-Co3O4) and Comparative Examples 1-3 are shown.
[0082] like Figure 8 As shown, the catalyst prepared by Ir-Co3O4 exhibits the smallest electrochemical impedance, demonstrating that it has the fastest reaction kinetic rate and electron transport capability.
[0083] Figure 9 The catalysts prepared for Example 1 (Ir-Co3O4) and Comparative Examples 1-3 at 10 mA / cm 2 Stability diagram of chronoelectric voltammetry under a current density of [value missing].
[0084] like Figure 9 As shown, the catalyst prepared by Ir-Co3O4 operates at 10 mA / cm². 2 It exhibits the best stability at current densities.
[0085] The above embodiments are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention.
Claims
1. A cobalt spinel electrocatalytic material modified with iridium single-points, characterized in that: in, The chemical formula of the iridium-modified cobalt spinel electrocatalytic material is abbreviated as: Ir-Co3O4. In the iridium-modified cobalt spinel electrocatalytic material, the iridium exists in the cobalt spinel in the form of unit dots. The preparation method of the iridium-modified cobalt spinel electrocatalytic material includes the following steps: Step 1: Cobalt chloride hexahydrate, anhydrous iridium chloride, and sodium chloride are initially mixed evenly in an agate mortar to obtain a mixed powder; Step 2: Grind the mixed powder and add sodium hydroxide solution to obtain a mixture; Step 3: Place the mixture in an oven to dry, grind the dried mixture again in an agate mortar, then place it in a muffle furnace and react at a predetermined temperature for a predetermined time, wash, and dry to obtain the iridium-modified cobalt spinel electrocatalytic material.
2. The cobalt spinel electrocatalytic material with iridium unit-point modification according to claim 1, characterized in that: in, The iridium-modified cobalt spinel electrocatalytic material has a nanosheet structure with a thickness of 2 nm to 4 nm. The atomic ratio of Ir, Co, and O in the iridium-modified cobalt spinel electrocatalytic material is 1.05:27.43:71.
52.
3. The cobalt spinel electrocatalytic material modified with iridium single-point according to claim 1, characterized in that: in, In step 1, the molar ratio of cobalt chloride hexahydrate and anhydrous iridium chloride, which are used as precursors, is 20:
1.
4. The cobalt spinel electrocatalytic material modified with iridium single-point according to claim 3, characterized in that: in, In step 1, the mass ratio of cobalt chloride hexahydrate to sodium chloride is 476 mg: 500 mg.
5. The cobalt spinel electrocatalytic material modified with iridium single-point according to claim 1, characterized in that: in, The specific process of step 2 is as follows: The mixed powder was placed in a high-energy ball mill jar and ball-milled at 500 rpm for 1 hour. Then, the sodium hydroxide solution was added, and the mixture was continued to be ball-milled at 500 rpm for 1 hour. The concentration of the sodium hydroxide solution is 4M. The mass-to-volume ratio of the mixed powder to the sodium hydroxide solution is (0.9g~1.1g):1mL.
6. The cobalt spinel electrocatalytic material modified with iridium single-point according to claim 1, characterized in that: in, In step 3, the mixture is placed in the oven and dried at a temperature of 60°C for 12 hours.
7. The cobalt spinel electrocatalytic material modified with iridium single-point according to claim 1, characterized in that: in, In step 3, the predetermined temperature is 350°C, the predetermined time is 6 hours, and the sintering gas in the muffle furnace is air.
8. An electrocatalyst, characterized in that, include: The cobalt spinel electrocatalytic material modified with iridium unit sites as described in any one of claims 1 to 7, and the carbon powder.
9. The electrocatalyst according to claim 8, characterized in that: in, The electrocatalyst is composed of the cobalt spinel electrocatalytic material modified with iridium unit sites and the carbon powder in a 1:1 mass ratio.
